Metagenomic comparison of gut communities between wild and captive Himalayan griffons - Wang, You; Zhai, Jundie; Tang, Boyu; Dong, Yonggang; Sun, Shengzhen; He, Shunfu; Zhao, Wenxin; Lancuo, Zhuoma; Jia, Qiangqiang; Wang, Wen (Frontiers in Veterinary Science, 2024)
Himalayan griffons (Gyps himalayensis), known as the scavenger of nature, are large scavenging raptors widely distributed on the Qinghai-Tibetan Plateau and play an important role in maintaining the balance of the plateau ecosystem. The gut microbiome is essential for host health, helping to maintain homeostasis, improving digestive efficiency, and promoting the development of the immune system. Changes in environment and diet can affect the composition and function of gut microbiota, ultimately impacting the host health and adaptation. Captive rearing is considered to be a way to protect Himalayan griffons and increase their population size. However, the effects of captivity on the structure and function of the gut microbial communities of Himalayan griffons are poorly understood. Still, availability of sequenced metagenomes and functional information for most griffons gut microbes remains limited. In this study, metagenome sequencing was used to analyze the composition and functional structures of the gut microbiota of Himalayan griffons under wild and captive conditions. Our results showed no significant differences in the alpha diversity between the two groups, but significant differences in beta diversity. Taxonomic classification revealed that the most abundant phyla in the gut of Himalayan griffons were Fusobacteriota, Proteobacteria, Firmicutes_A, Bacteroidota, Firmicutes, Actinobacteriota, and Campylobacterota. At the functional level, a series of KEGG (Kyoto Encyclopedia of Genes and Genome) functional pathways, CAZymes (carbohydrate-active enzymes) categories, VFGs (virulence factor genes), and PHI (pathogen-host interactions) were annotated and compared between the two groups. In addition, we recovered nearly 130 MAGs (metagenome-assembled genomes). In summary, the present study provided a first inventory of the microbial genes and metagenome-assembled genomes related to the Himalayan griffons, marking a crucial first step towards a wider investigation of the scavengers microbiomes with the ultimate goal to contribute to the conservation and management strategies for this near threatened bird.